Systematic Review of Lightweight Cryptographic Algorithms for IoT Security: Advances and Trends - A, Shilpa Shetty; B, Sudeepa K; M, Chaithra K; G, Ananth Prabhu (Universitas Ahmad Dahlan, 2025)
The proliferation of the Internet of Things (IoT) has fundamentally transformed modern infrastructure, but has also intensified security risks due to device resource constraints and interconnected environments. This systematic review synthesizes research on lightweight cryptographic algorithms for IoT security, focusing on studies published from 2019 to 2025. Relevant articles were identified through comprehensive searches of IEEE Xplore, ScienceDirect, Springer, and ACM Digital Library using Boolean strings that targeted terms including “lightweight cryptography,” “IoT security,” “side-channel resistance,” and “NIST LWC Standard.” Only peer-reviewed works in English addressing cryptographic primitives suitable for constrained IoT platforms were included; gray literature and studies without benchmarking on IoT-class hardware were excluded. Selection adhered to PRISMA guidelines to reduce selection bias. This review maps algorithmic taxonomies, highlights advances such as ASCON (NIST LWC 2025), side-channel and post-quantum resistance, and discusses real-world hardware-software trade-offs. Limitations arise from database scope, language constraints, and potential exclusion of emerging industry preprints. The analysis identifies persistent gaps—side-channel mitigations, context-aware security, and privacy—with guidance for future research. Overall, the findings clarify current capabilities and boundaries, supporting the development of scalable, energy-efficient, and robust cryptographic frameworks for secure IoT deployments within documented methodological limits.